2013
DOI: 10.1371/journal.pone.0082596
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Small Auxin-Up RNA (SAUR)-Like Gene Involved in Arabidopsis thaliana Development

Abstract: The root of Arabidopsis thaliana is used as a model system to unravel the molecular nature of cell elongation and its arrest. From a micro-array performed on roots that were treated with aminocyclopropane-1-carboxylic acid (ACC), the precursor of ethylene, a Small auxin-up RNA (SAUR)-like gene was found to be up regulated. As it appeared as the 76th gene in the family, it was named SAUR76. Root and leaf growth of overexpression lines ectopically expressing SAUR76 indicated the possible involvement of the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 67 publications
1
46
0
Order By: Relevance
“…Previous studies have shown that ectopic expression of several SAUR family genes resulted in elongated hypocotyls in the light and that plants overexpressing SAUR19 exhibited opened cotyledons in the dark (23)(24)(25). However, several other SAURs have been suggested to inhibit cell expansion in certain organs (26)(27)(28). To test the effects of lirSAURs on plant growth, we generated transgenic lines overexpressing SAUR14, SAUR50, and SAUR65, which were selected to represent classes 1, 2, and 3, respectively.…”
Section: Saur Family Genes Exhibit Remarkably Organ-specific Light-mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that ectopic expression of several SAUR family genes resulted in elongated hypocotyls in the light and that plants overexpressing SAUR19 exhibited opened cotyledons in the dark (23)(24)(25). However, several other SAURs have been suggested to inhibit cell expansion in certain organs (26)(27)(28). To test the effects of lirSAURs on plant growth, we generated transgenic lines overexpressing SAUR14, SAUR50, and SAUR65, which were selected to represent classes 1, 2, and 3, respectively.…”
Section: Saur Family Genes Exhibit Remarkably Organ-specific Light-mentioning
confidence: 99%
“…Based on microarray analysis, about half of SAURs are up-regulated by auxin treatment in Arabidopsis (22). Overexpression of several distinct SAUR genes resulted in increased growth of cotyledons, hypocotyls, or roots, respectively (23)(24)(25), whereas a few SAURs have been suggested to negatively regulate cell growth in specific organs (26)(27)(28). Recently, it has been found that SAURs could interact with D-clade type 2C protein phosphatase (PP2C) proteins to inhibit their phosphatase activities, therefore activating…”
mentioning
confidence: 99%
“…For instance, one locus on chromosome 6 (366330) for RL0510 in control (Supplemental Table S9) was within the SCARECROW (SCR) gene that regulates radial root and shoot anatomy and root hair tip growth through cell division and differentiation (Gao et al, 2004). One locus on chromosome 1 (40526762) for RV in control was within the OsSAUR3 gene, an early auxin-responsive gene that regulates root elongation (Markakis et al, 2013). The two homologs of this gene were close (OsSAUR25 = 11 kb and OsSAUR26 = 42 kb) to the locus on chromosome 6 (27819933) for MRL in control (Supplemental Table S9).…”
Section: A Priori Candidate Genes Underlying the Genetic Loci Of Phenmentioning
confidence: 99%
“…SAUR76 is highly expressed in roots, but only weakly expressed in leaves. Interestingly, while auxin treatment resulted in a dramatic upregulation in roots, no increase in SAUR76 expression was observed in leaves (Markakis et al, 2013). When overexpressed from the 35S promoter, SAUR76 conferred a reduction in leaf size.…”
Section: Introductionmentioning
confidence: 99%